2014
DOI: 10.1159/000358829
|View full text |Cite
|
Sign up to set email alerts
|

Human Granulosa Cells: Insulin and Insulin-Like Growth Factor-1 Receptors and Aromatase Expression Modulation by Metformin

Abstract: Background/Aim: Granulosa cells are the source of the most important ovarian steroids. Even in patients without significant improvement in metabolic parameters, metformin has apparently an important effect on the ovary. The aim of this study was to evaluate gene and protein expression of an insulin receptor (IR), insulin-like growth factor-1 (IGF1) receptor (IGF1R) and aromatase in granulosa cells treated with metformin and insulin. Methods: Luteinized granulosa cells were collected from 27 patients during in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…One of these target tissues is the granulosa cells in the ovaries. Metformin changes the insulin‐dependent metabolism of glucose in granulosa cells, and decreases ovarian sensitivity to FSH, possibly ameliorating the response to COS.…”
Section: Resultsmentioning
confidence: 99%
“…One of these target tissues is the granulosa cells in the ovaries. Metformin changes the insulin‐dependent metabolism of glucose in granulosa cells, and decreases ovarian sensitivity to FSH, possibly ameliorating the response to COS.…”
Section: Resultsmentioning
confidence: 99%
“…The PCOS is characterized by elevated levels of insulin and IGF-1R [42] and it has been hypothesized that this could influence the pathogenesis of the syndrome and the alterations of sexual steroids commonly frequent in patients affected by PCOS. IGF-1R is present on the cellular membrane of hGCs [43] and it has been demonstrated that different insulin sensitizer drugs such metformin are able to modulate gene expression [20, 44]. …”
Section: Discussionmentioning
confidence: 99%
“…Insulin has been reported to be able to interact with steroidogenic enzymes in granulosa and luteinic cells of the ovaries [1620]. Specifically insulin seems to potentiate the FSH and luteinizing hormone (LH) induction of cytochrome P450 family 19 subfamily A member 1 ( CYP19A1 ) aromatase and this effect has been shown to be so evident that insulin is considered by many as a co-gonadotrophin [1719, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Culture of luteinized granulosa cells exposed to the pre-ovulatory LH surge and with metformin lowers progesterone and estradiol syntheses in the same manner as non-luteinized granulosa cells exposed to either FSH or insulin ( 85 ). Rice et al and Fuhrmeister et al have demonstrated, that metformin induces a decrease in estradiol synthesis via the inhibition of aromatase expression by the MAPK signaling pathway ( 86 , 87 ). However, metformin also induces activation of insulin-dependent AMPK pathways involved in lactate production by human granulosa cells ( 88 , 89 ).…”
Section: Metformin and Steroidogenesismentioning
confidence: 99%